Early sex determination of Turkey by observation of differences in body weight between male and female (Progressive Agriculture, 2021)
The present study was conducted to determine the early sex in turkeys by observation of the differences in body weight between male and female birds. A total of 30-day old black color unsexed poults having almost similar body weight at hatching were considered for the experimentation and housed at the Poultry Farm of Bangladesh Agricultural University, Mymensingh-2202, Bangladesh. All birds were reared up to 12 weeks of age under intensive management with supplementation of commercial broiler starter and grower feeds. Birds were reared under similar management conditions. Significantly higher (p